Financial Literacy as A Catalyst of Inclusive and Sustainable Growth - Soreng, Manisha; Meena, R.S. (Journal of Economics and Management, 2026)
Financial literacy has emerged as a critical driver of inclusive and sustainable economic growth, particularly in developing and emerging economies. This study examines how financial knowledge, skills, and attitudes empower individuals to make informed financial decisions, thereby enhancing financial inclusion and long-term economic stability. By improving individuals’ ability to access, manage, and utilize financial services effectively, financial literacy contributes to poverty reduction, income equality, and resilience against economic shocks. Furthermore, it supports sustainable growth by encouraging responsible consumption, savings behavior, and investment in productive activities. The study highlights the role of policymakers, educational institutions, and financial organizations in promoting financial literacy through targeted programs and digital financial education initiatives. The findings suggest that strengthening financial literacy frameworks can bridge socio-economic disparities and foster a more inclusive financial ecosystem, ultimately contributing to sustainable national development.